Semiconductors (LEDs) quality control based in high-resolution 3D X-ray microscope (Brazilian Journal of Radiation Sciences, 2022)
Electronic devices are getting smaller each time and the technology, increasingly complex. Commonly found problems such as reflow soldering and open solder connections, which are mostly difficult to detect by conventional means like X-ray images or physical cut on the transverse section. Along with the challenge of finding these flaws, there are also some problems that may arise on the exposure of them using destructive analysis techniques, such as the fiscal transversal cut and chemical decapsulation. Both techniques may induce damage not relevant to where that flaw is located or remove evidence of a flaw or a damaged place. The high-resolution 3D x-ray computerized microtomography provides a powerful alternative solution and non-invasive to issues that involve the analysis of semiconductor devices. This research contemplates the study of semiconductor’s integrity (LED’s) based of X-ray computerized microtomography. The SkyScan 1272 Bruker commercial equipment was used for analysis of the P-N junction in a set with 10 LEDs, under non polarized conditions and upon electrical overstress effects on its contact terminals. The P-N junction had their dimensions analyzed on the three spatial directions (x, y and z) and studied on the effects that occur when a LED is damaged. The study methodology of integrity regarding computerized microtomography have shown consist outcomes that allowed the understanding of what occurs on the LED's structure and investigates matters that allows decisions to be made regarding its quality, and so, accomplishing the goals designated on this research.